2004
DOI: 10.1038/labinvest.3700107
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and passage of transthyretin through the blood-nerve barrier in recipients of familial amyloid polyneuropathy livers

Abstract: Familial amyloid polyneuropathy (FAP) is characterized by deposition of mutated transthyretin (TTR) in the peripheral nervous system. Prior to amyloid fibrils, nonfibrillar TTR aggregates are deposited inducing oxidative stress with increased nitration (3-NT). As the major source of TTR is the liver, liver transplantation (LT) is used to halt FAP. Given the shortage of liver donors, domino LT (DLT) using FAP livers is performed. The correlation between TTR deposition in the skin and nerve was tested in biopsie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 27 publications
3
46
0
3
Order By: Relevance
“…Previous studies have shown either amyloid or TTR deposits at different gastrointestinal levels as early as 3 years after DLT. 16,17 In our experience, this kind of deposit is quite common (37% of the evaluated patients), and the longer follow-up for our group of patients is likely to have influenced this finding. Asymptomatic FAP patients with the Val30Met mutation have TTR deposits in the form of nonfibrillar aggregates in some organs years before the disease develops.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous studies have shown either amyloid or TTR deposits at different gastrointestinal levels as early as 3 years after DLT. 16,17 In our experience, this kind of deposit is quite common (37% of the evaluated patients), and the longer follow-up for our group of patients is likely to have influenced this finding. Asymptomatic FAP patients with the Val30Met mutation have TTR deposits in the form of nonfibrillar aggregates in some organs years before the disease develops.…”
Section: Discussionmentioning
confidence: 73%
“…16,17 Yamamoto et al 18 showed the development of impaired nerve conduction in DLT recipients but without clinical correlations or biopsy samples. Recently, 3 cases of the transmission of systemic TTR amyloidosis were published.…”
Section: Discussionmentioning
confidence: 99%
“…There was no evidence of peripheral or autonomic neuropathy 12-40 months after DLT, and gastrointestinal biopsies showed no signs of de novo amyloid deposits 4-24 months after DLT (9). In Portugal, 15 DLT recipients had skin biopsies performed 1-7 years after DLT and TTR depositions were found in a minority of patients 3 years after transplantation (10). A summary of the previous reports is shown in Table 1 (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 94%
“…In Portugal, 15 DLT recipients had skin biopsies performed 1-7 years after DLT and TTR depositions were found in a minority of patients 3 years after transplantation (10). A summary of the previous reports is shown in Table 1 (9)(10)(11)(12)(13). The possibility of de novo amyloidosis as a late complication of DLT is a worrisome issue, and more information is needed to optimize the selection of DLT recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Development of FAP symptoms has not been reported in any of the domino recipients at up to 7 years follow-up worldwide. However, Sousa et al reported that fibrillar deposits of TTR were observed in the epineurium of the biopsied peripheral nerve in a domino recipient with a 6-year post-operative history (31). Serial and careful follow-up of domino recipients is necessary.…”
Section: Discussionmentioning
confidence: 99%